'Be Clear on Cancer': the impact of the UK National Bowel Cancer Awareness Campaign. (29th August 2013) - Peacock, O.; Clayton, S.; Atkinson, F.; Tierney, G. M.; Lund, J. N.
Abstract: Aim: The National Bowel Cancer Awareness Campaign ('Be Clear on Cancer') was launched by the UK government in January 2012, encouraging people with bowel symptoms to present to primary care. Our aim was to evaluate the impact of the campaign on colorectal services in secondary care. Method: Suspected cancer 2‐week‐wait (2WW) patients 3 months before and 3 months after the launch of the campaign were included. Demographics, reason for referral, investigations performed, cost analysis and eventual diagnoses were collected. Results: Three hundred and forty‐three patients [median age 70 (36–100) years, 194 (57%) women] were seen and investigated in the 3 months prior to the launch of the campaign at an average cost of £575 per patient. Twenty‐seven (8%) were diagnosed with lower gastrointestinal cancer and 29 (8%) with polyps. In the 3 months following the launch, 544 patients [median age 68 (30–92) years, 290 (53%) women] were reviewed (59% increase; P = 0.004). The 'did not attend' rate fell from 10% to 1%. Thirty‐two (6%) patients were diagnosed with a lower gastrointestinal cancer and 20 (4%) with colorectal polyps. The cost per colorectal cancer detected rose from £7585.58 before the campaign to £9662.72 after launch ( P = 0.04). Conclusion: The 'Be Clear on Cancer' campaign has substantially increased the number of referrals under the 2WW rule, but mainly in the worried well. This has increased demands on both resources (59% more tests) and finance. Cost per cancer detected rose by 27% with no increase in funding to support the increased activity.